The unbalanced imagery of anti-terrorism policy - Stuart Macdonald (Cornell Journal of Law and Public Policy, 2009)
Balancing the competing demands of security and liberty is commonly said to be the central task in anti-terrorism policy. This article begins by distinguishing two ways in which the notion of balance is presented – the trade-off thesis and the image of a set of scales – and argues that each is flawed as an analytical aid. It then goes on to show further limitations of the balancing discourse – it excludes any scope for consideration of the effect a particular measure will have on security and liberty and of issues relating to the allocation of resources, and it focuses on just one strategy for responding to terrorism. The article concludes by warning against the use of imagery in complex debates and by claiming that balancing the demands of security and liberty is not the sole, or even the central, task in anti-terrorism policy.